Systematic identification of type I and type II interferon-induced antiviral factors - Liu, Su-Yang; Sanchez, David Jesse; Aliyari, Roghiyh; Lu, Sun; Cheng, Genhong (Proceedings of the National Academy of Sciences - PNAS, 2012)
Type I and type II interferons (IFNs) are cytokines that establish the cellular antiviral state through the induction of IFN-stimulated genes (ISGs). We sought to understand the basis of the antiviral activity induced by type I and II IFNs in relation to the functions of their ISGs. Based on gene expression studies, we systematically identified antiviral ISGs by performing blinded, functional screens on 288 type I and type II ISGs. We assessed and validated the antiviral activity of these ISGs against an RNA virus, vesicular stomatitis virus (VSV), and a DNA virus, murine gammaherpes virus (MHV-68). Overall, we identified 34 ISGs that elicited an antiviral effect on the replication of either one or both viruses. Fourteen ISGs have uncharacterized antiviral functions. We further defined ISGs that affect critical life-cycle processes in expression of VSV protein and MHV-68 immediate-early genes. Two previously undescribed antiviral ISGs, TAP1 and BMP2, were further validated. TAP1-deficient fibroblasts were more susceptible to VSV infection but less so to MHV-68 infection. On the other hand, exogenous BMP2 inhibits MHV-68 lytic growth but did not affect VSV growth. These results delineate common and distinct sets of type I and type II IFN-induced genes as well as identify unique ISGs that have either broad or specific antiviral effects on these viruses.